Endometriosis leading to frequent emergency department visits-women's experiences and perspectives. - Christine Roman Emanuel; Herborg Holter; Ida Nygren Hansson; Maria Forslund (PLoS ONE)
Background Endometriosis is a common condition affecting 1-10% of all women. The condition is highly associated with pain. Most women with endometriosis are treated as elective outpatients, but these patients sometimes need to visit the emergency department. The aim of this study was to describe experiences and expectations related to repeated gynaecological emergency (GED) visits among women with endometriosis. Method This qualitative study with semi structured interviews were conducted with ten patients diagnosed with endometriosis who visited the GED at a tertiary university hospital four or more times within a 12-month period. Data were analysed by thematic content analysis. Result Two main themes was identified which embodied the women's overall experience, grouped into: "Living with pain" and "Patients´ needs when seeking GED", with six underlying themes. Several women described their visit to the GED as a "lottery", as they never knew what kind of treatment they would receive. Being listened to was most important for the women. Individualized care plans did not exist for most of the women in this study, although they repeatedly needed to visit the GED.